PENGARUH MAGANG KEPENDIDIKAN 3 DAN LINGKUNGAN KELUARGA TERHADAP MINAT MENJADI GURU PADA MAHASISWA PAP FKIP UNS - Stefany Shintya Paulina; Hery Sawiji; Tri Murwaningsih Murwaningsih (JIKAP (Jurnal Informasi Dan Komunikasi Administrasi Perkantoran), 2020)
The purpose of this research was to determine the effect of 1) educational apprenticeship 3 on the interest in becoming a teacher in students of Office Administration Education Study Program, FKIP UNS 2) family environment on the interest in becoming a teacher in students of Office Administration Education Study Program, FKIP UNS and 3) educational apprenticeship 3 and family environment together on the interest in becoming a teacher in students of Office Administration Education Study Program, FKIP UNS. The population in this research were all college students of Office Administration Education Study Program, FKIP UNS year 2015 as many as 51 students. The sample in this research as many as 51 students, using a saturated sampling technique. Data collection technique used in this research were questionnaire and document analysis. The data were analyzed using multiple regression analysis, t-test and F-test. This research concludes that there is a positive and significant effect of 1) educational apprenticeship 3 on the interest in becoming a teacher in students of Office Administration Education Study Program FKIP UNS. 2) family environment on the interest in becoming a teacher in students of Office Administration Education Study Program FKIP UNS, and 3) educational apprenticeship 3 and family environment together on the interest in becoming a teacher in students of Office Administration Education Study Program FKIP UNS.